Prerequisites, Strategies and Consequences of Implementing Ethical Management in Sports of Iran - Sayedeh Shirin Derakhshandeh; Hassan Fahim Devin; Hossein Peymanizad; Mohammadreza Ismaeelzadeh (Islamic Azad university, Isfahan Branch, 2022)
Objective: The purpose of this study was to identify the preconditions, strategies and consequences of implementing ethical management in sports in the country based on data theory and provide a model.Methodology: The present research is applied research in terms of purpose and qualitative in terms of data search and based on data theory and in terms of analytical-exploratory data analysis method and in terms of time of research is present-type. The information was collected in the field method. The statistical population of the study includes all sports experts in the country. The statistical sample was purposeful and finally interviewed with 35 people. Data collection was done through semi-organized and exploratory interviews with sports experts in the country. Foundation data analysis methods were used to analyze the data. Results: The results showed that the concepts obtained from coding signs in the category of predecessors include 17 items in two categories of organizational and extra-organizational concepts, in the category of strategies including 43 items and three categories of organizational strategies, group strategies and individual-personality strategies and concepts. Regarding the future, 29 items were divided into three categories: micro-level (individual), medium-level (group) and macro-level (organization).Conclusion: The country's sports managers can use the concepts obtained to implement ethical management in sports and the implementation of ethical management in the country's sports causes the effectiveness of individual, group and organizational activities in order to achieve organizational goals.